Asymmetric interspecific competition drives shifts in signalling traits in fan-throated lizards. Issue 1940 (9th December 2020) - Zambre, Amod M.; Khandekar, Akshay; Sanap, Rajesh; O'Brien, Clairissa; Snell-Rood, Emilie C.; Thaker, Maria
Abstract : Interspecific competition can occur when species are unable to distinguish between conspecific and heterospecific mates or competitors when they occur in sympatry. Selection in response to interspecific competition can lead to shifts in signalling traits—a process called agonistic character displacement. In two fan-throated lizard species— Sitana laticeps and Sarada darwini —females are morphologically indistinguishable and male agonistic signalling behaviour is similar. Consequently, in areas where these species overlap, males engage in interspecific aggressive interactions. To test whether interspecific male aggression between Si. laticeps and Sa. darwini results in agonistic character displacement, we quantified species recognition and signalling behaviour using staged encounter assays with both conspecifics and heterospecifics across sympatric and allopatric populations of both species. We found an asymmetric pattern, wherein males of Si. laticeps but not Sa. darwini showed differences in competitor recognition and agonistic signalling traits (morphology and behaviour) in sympatry compared with allopatry. This asymmetric shift in traits is probably due to differences in competitive abilities between species and can minimize competitive interactions in zones of sympatry. Overall, our results support agonistic character displacement, and highlight the role of asymmetric interspecific competition in driving shifts in social signals.